Konstitusi Peralihan Kekuasaan Kesultanan Kutai Kartanegara Ing Martapura - Syamsuri Syamsuri (Madika: Jurnal Politik dan Governance, 2021)
ideology of state sovereignty, which was adhered to by the royal leaders and their people. The infrastructure of civilization is still sustainable, despite the turmoil of the succession of leadership, indicating the presence of very strong social capital, namely justice and peace. Starting from the archipelago ideology is Kutai Martapura Kingdom, switching to a Malay ideology is Kutai Kartanegara Kingdom, and a modern ideology is Kutai Kartanegara Ing Martapura Sultanate. The nationality theory ('ashabiyah), the urban theory ('urban), and the development theory ('umran) by Ibn Khaldun (1332 - 1406 AD), were able to reveal the dynamics of the historical continuity of the Republic of Indonesia, which wanted to move the State Capital in some areas Kutai Kartanegara Regency, East Kalimantan Province. Taking turns, coming and going, until the population settles in an area in the territory of the country, shows the presence of a very great human culture